The Influence of Assemblr Edu to Improve Knowledge of Parenteral Medication Among Nursing Students in Yogyakarta Nursing College, Indonesia - Istichomah, Istichomah; Bin Sansuwito, Tukimin (International Journal of Health Sciences, 2024)
Parenteral medication administration errors among nursing students are most common in nursing laboratories and health services. This will be dangerous for patients as well as for students. Efforts to improve students' knowledgeand skills continue to be developed by nursing education in Indonesia. One form of educational media development is Assemblr edu. By using Assemblr edu about parenteral medication, it is hoped that students can access easily and quickly. The research is a quasi-experimental study with a non-equivalent group pre-test and post-test designed with control group. This research to examine the effectivities of Assemblr edu parenteral medication on knowledge and skill among nurse student. In a two-group experiment using pretest-posttest methodology with an added comparison group, the intervention group in the first group received Assemblr edu while the control group get manual modul of parenteral medication. The research location at three nursing College in Yogyakarta.Respondents in this study in each group were 56, so the total respondents were 112 students. Statistic test shows thant the Sig. (2-Tailed) value from the Independent Sample t-test as 0.000 or <0.05, indicating a difference in the mean scores between the post-test measurements of knowledge and skills in the control and experimental groups. Based on this Sig. (2-Tailed) value, it can be interpreted that there is a significant relationship regarding the effectiveness of Assemblr Edu Augmented Reality in improving the knowledge and skills of parenteral medication among nursing students at Yogyakarta Nursing College, Indonesia.There was a difference in the pre-post test scores related to knowledge in administering medication via parenteral routes between the control and intervention groups.